The use of bioactive cements in the endodontic treatment of the deciduous and permanent dentition: a systematic review - M.D. Anastasio; A. Mastroianni; A.V. Brescia; C. Gisondi; R. Docimo (Publymed, 2024)
Bioactive cements are indicated in many treatments of pediatric dentistry. The present study aims to analyze the efficacy of bioactive cements, in endo-pedodontics, both in deciduous dentition (vital teeth) and in permanent dentition (vital and necrotic teeth with immature apex), comparing them with other endodontic materials on the market. ( 2) Materials and methods: The study was prepared according to PRISMA guidelines using databases such as: Medline, Pubmed, Cochrane. In vivo studies performed within the last ten years were included. ( 3) Results: The research initially collected 762 scientific articles of which 28 were excluded as duplicates and 701 following analysis of abstracts and titles, according to the exclusion criteria of the present study. 33 full-text papers were examined, 25 of which were excluded according to the eligibility criteria. Therefore, only 8 studies were included for qualitative analysis and data mining. ( 4) Conclusion: Bioactive cements can be considered first choice materials in endopedodontics due to their chemical-biological characteristics and long-term prognosis. However, in the treatment of the necrotic permanent tooth with an immature apex, pulp regeneration procedures show significantly superior results compared to apecification techniques, especially in terms of root length and thickness.